Maintenance Policies of Single and Multi-Unit Systems in the Past and Present - Sarkar, Asis; Suresh Kumar, E. (Asian Review of Mechanical Engineering, 2012)
This paper surveys the literature related to maintenance policies for single and multi-unit systems. The emphasis is on work appearing in different periods. The literature is divided into two main categories single and multi unit system. The single unit system is divided into six sub-categories like: Agedependent, Periodic, Failure limit policy, Sequential, Repair limit, Repair number counting and reference time policy. Similarly policies of multi-unit are divided into two subcategories; viz Group and Opportunistic maintenance policies; Each kind of policy has different characteristics, advantages and disadvantages with lot of contributions from Research scientist and Technologists. Around 150 authors and their research works are presented in the reference section. It will help the reader to select the exact policy for their organization and the reference section will be helpful for further study and further knowledge about different existing maintenance practices.